Penelitian pengaruh penambahan kompon PVC pada komon karet untuk sol - Titien Sayekti et. al. (Majalah Kulit, Karet, dan Plastik, 1988)
PVC, is polymer of vinyl chloride, is added to rubber as reinforcing agent will improve the hardness, modulus and tensile strength of rubber products as observed in this experiments.By adding 40 parts of PVC compound, the highest value of tensile strength and hardness of the products are 94,0471 kg/cm2 for tensile strength and 54,6666 shore A for hardness.